Equalisation of Children‘s Various Levels of Physical Activity Using Increased Physical Activity at School Among Ninth Graders - Lomsdal, Hege Hov; Lomsdal, Sondre Arntzen Arntzen; Lagestad, Pål (Frontiers in Public Health, 2022)
The purpose of this study was to examine whether 60 min of physical activity implemented during school hours, would have an impact on 15-year-olds' MVPA (moderate to vigorous physical activity) throughout the school day, and what effect it would have on low-, average-, and high- physically-active students. The intervention study included a sample of every 93 students in the ninth grade from a school in Trøndelag, Norway. Data on the students' physical activity levels during schooltime were measured using accelerometers and analyzed using the Actilife program. A significant higher change in MVPA was found in the intervention group compared to the control group, with an average increase of 25 min in MVPA in the pre-test to 42 min in post-test. Further analyses showed that the that both the low-active and the high-active had a significant increase in MVPA, taking the results of the control group into consideration. However, the low-active participants had the largest increase, with a 123% increase in MVPA during schooltime. The implication of the study is that PA interventions in school have the largest percentage effect among the low-active students in the study, which indicates that school-based interventions can be important in bridging social differences in MVPA among adolescents.